2015
DOI: 10.1016/j.eururo.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence Patterns After Open and Robot-assisted Radical Cystectomy for Bladder Cancer

Abstract: Background Concerns remain whether robot-assisted radical cystectomy (RARC) compromises survival because of inadequate oncologic resection or alteration of recurrence patterns. Objective To describe recurrence patterns following open radical cystectomy (ORC) and RARC. Design, setting, and participants Retrospective review of 383 consecutive patients who underwent ORC (n = 120) or RARC (n = 263) at an academic institution from July 2001 to February 2014. Intervention ORC and RARC. Outcome measurements a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
93
4
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(107 citation statements)
references
References 28 publications
(35 reference statements)
3
93
4
7
Order By: Relevance
“…This thoughtprovoking retrospective evidence raised many criticisms and concerns on RARC. Though similar rates of unusual metastatic dissemination were observed, the trend showed that uBCa in RARC patients more often did recur in extrapelvic nodal sites and with peritoneal carcinomatosis [13]. However, in a detailed analysis from the same institution, atypical dissemination was found to be dictated by tumor biology rather than surgical aspects [14].…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…This thoughtprovoking retrospective evidence raised many criticisms and concerns on RARC. Though similar rates of unusual metastatic dissemination were observed, the trend showed that uBCa in RARC patients more often did recur in extrapelvic nodal sites and with peritoneal carcinomatosis [13]. However, in a detailed analysis from the same institution, atypical dissemination was found to be dictated by tumor biology rather than surgical aspects [14].…”
Section: Introductionmentioning
confidence: 84%
“…Atypic metastatic location was defined according to the previous study by Nguyen et al [13] and consisted of clinical or pathologic evidence of peritoneal carcinomatosis and extrapelvic lymph node metastasis. First, means, medians, and interquartile ranges (IQR) or frequencies and proportions were reported for continuous or categorical variables on the study populations respectively.…”
Section: Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Khan et al [9] showed an overall survival of 64%, disease-specific survival of 75%, and disease-free survival of 50% after RARC at minimum of 5 years follow up. Furthermore, RARC is not known to act as an independent predictor of recurrence [10].There has been much debate on the suitable approach for urinary diversion (intracorporeal or extracorporeal) following RARC. Intracorporeal urinary diversion (ICUD) has the potential advantages of a small incision, decreased bowel exposure and less post-operative pain.…”
mentioning
confidence: 99%
“…Khan et al [9] showed an overall survival of 64%, disease-specific survival of 75%, and disease-free survival of 50% after RARC at minimum of 5 years follow up. Furthermore, RARC is not known to act as an independent predictor of recurrence [10].…”
mentioning
confidence: 99%